Height loss with advancing age in a hospitalized population of Polish men and women: magnitude, pattern and associations with mortality - Chmielewski, Piotr; Borysławski, Krzysztof; Chmielowiec, Krzysztof; Chmielowiec, Jolanta (Anthropological Review, 2015)
The connection between the rate of height loss in older people and their general health status has been well documented in the medical literature. Our study was aimed at furthering the characterization of this interrelationship in the context of health indices and mortality in a hospitalized population of Polish adults. Data were collated from a literature review and from a longitudinal study of aging carried out in the Polish population which followed 142 physically healthy inmates, including 68 men and 74 women, for at least 25 years from the age of 45 onwards. Moreover, cross-sectional data were available from 225 inmates, including 113 men and 112 women. These subjects were confined at the same hospital. ANOVA, t-test, and regression analysis were employed. The results indicate that the onset of height loss emerges in the fourth and five decade of life and there is a gradual acceleration of reduction of height at later stages of ontogeny in both sexes. Postmenopausal women experience a more rapid loss of height compared with men. The individuals who had higher rate of loss of height (≥3 cm/decade) tend to be at greater risk of cardiovascular events and all-cause mortality. In conclusion, our findings suggest that a systematic assessment of the rate of loss of height can be useful for clinicians caring for elderly people because of its prognostic value in terms of morbidity and mortality.